The Criteria of Underground Rock Structure Failure and Its Implication on Rockburst in Roadway: A Numerical Method - Xiaofei Guo; Zhiqiang Zhao; Xu Gao; Zhenkai Ma; Nianjie Ma (Shock and Vibration)
Rockburst in roadway happened along with a large-scale destruction of the surrounding rock. To study the failure laws of the surrounding rock in the process of rockburst in roadway, the evolution behaviors of the plastic zone and the criteria of large-scope failure were studied by using FLAC numerical simulation. Meanwhile, the stress response laws of the plastic zone were studied by loading or unloading in a single direction. The results showed that, in the 20 MPa stress environment, large-scale failure zone would appear when the maximum confining pressure was loaded to 50 MPa or the minimum confining pressure was unloaded to 6 MPa. Loading in the direction of maximum confining pressure or unloading in the direction of minimum confining pressure, when the stresses reached a certain limit, could lead to a large-scale expansion to the failure zone of the surrounding rock a roadway. Meanwhile, the stress response of the plastic zone became more sensitive, which might easily trigger rockburst in roadway. In addition, two sine qua nonstress conditions for rockburst in roadway were determined: high stress ratio and high stress level. This might provide a theoretical basis for the stress source mechanism of roadway rockburst.